The impact of information on prices: the case of Blanco y Negro - Avendaño, Luis; Rodríguez, Arturo (Estudios de Administración, 2009)
Blanco y Negro publicly traded allows us to analyze the impact of information on stock prices. Our study analyses the period between 2005 and 2009 which includes nine tournaments. Controlling for the expected game result by using the betting market, we find that investors react asymmetrically to wins and losses. Specifically, unexpected losses induce significantly abnormal returns, while unexpected wins or expected results have an insignificant effect on stock performance.